PENGARUH KUALITAS PELAYANAN, PROMOSI, DAN HARGA TERHADAP KEPUASAN PELANGGAN NINJA EXPRESS - Tommy, Bagg; Nasruji, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2024)
This research titled is The Influence of Service Quality, Promotion, and Price on Customer Satisfaction at Ninja Express Bengkong Branch Batam City and aims to determine the influence between those related variables. This research uses quantitative method with data obtained from distributing questionnaires and the resulting data is proceesed using the SPSS application. The sample in this research was obtained from The Yount Formula with 77 sample of respondents. The result of this research are Service Quality variable with tcount 2.175 > ttable 1.99210, Promotion variabel with tcount 3.569 > ttable 1.99210, and Price variabel with tcount 0.926 < ttable 1.99210, which indicates that the first and second hypotheses are accepted, while the third was rejected. Apart from that, Service Quality, Promotion and Price have a simultaneous effect by showing the result Fcount 19,761 > Ftable 2,730 and the R2 value of 44.80%, which indicates that the Customer Satisfaction variable is influenced by 44.8% by Service Quality, Promotion and Price, while 55.20% others are influenced by other variables outside of the research.